English Enhancement Training Program for Employees: Basis for a Guidebook on Employees’ Enrichment of Communication Skills - Argelyn Diengo; Jeffrey Astillero (International Journal on Integrated Education, 2026)
This study evaluated the effectiveness of an English Enhancement Training Program (EETP) as a basis for developing a guidebook for the enrichment of employees’ communication skills in the workplace. Using a quantitative quasi-experimental one-group pretest–posttest design, 30 purposively selected employees from the Human Resources, Accounting, and Operations departments of a private security agency participated. The EF Standard English Test measured reading and listening, while CEFR-aligned rubrics assessed speaking and writing. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test at a 0.05 level of significance. Results showed moderate proficiency in the pretest, with speaking as the weakest skill. Posttest results revealed improvements across all macro skills, with significant gains in reading, speaking, and writing, while listening improved but was not statistically significant. The findings indicate that the EETP is an effective intervention and served as a basis for developing a guidebook with structured, task-based activities to enhance workplace communication skills.